External hernia of the supravesical fossa: Rare or simply misidentified?. (May 2017) - Amato, G.; Romano, G.; Erdas, E.; Medas, F.; Gordini, L.; Podda, F.; Calò, P.
Abstract: Background: External hernias of the supravesical fossa are considered rare, perhaps wrongly. Highlighting clinical and anatomical features could be useful for correct, preoperative diagnosis, thus avoiding the risk of complications such as incarceration. The study aims to demonstrate that the incidence of external protrusions of the supravesical fossa is higher that supposed. Probably, being mistaken for direct hernias, these hernia types are misidentified and not included in current classifications. This issue deserves attention due to the elevated risk of incarceration related to its distinctive structure. Material and methods: 249 consecutive open anterior inguinal hernia procedures were analyzed. Hernias were categorized according to the Nyhus classification. A subgroup of direct hernias involved true hernias of the supravesical fossa. Multiple ipsilateral, as well as combined hernias having a multi-component structure, were also considered. Results: 13 true hernias of the supravesical fossa and 19 multiple ipsilateral or combined hernias composed of direct and/or indirect hernia, together with one hernia of the supravesical fossa were identified. 4 true hernias of the supravesical fossa presented signs of incarceration. In three other combined protrusions, the herniated component of the supravesical fossa also showed incarceration of the visceral content. Conclusions: Hernias of the supravesical fossa would appear to be more frequent than imagined. These protrusions show a diverticular shape and the base is often tightened by the stiffer medial umbilical fold. This explains the apparently higher tendency to incarceration that distinguishes this hernia type. Preoperative signs of inguinal pain and irreducibility are pathognomonic for correct diagnosis. In these cases, surgical treatment in the short term is recommended. Highlights: The study aims to provide the surgical community with clinical data concerning hernias of the supravesical fossa. Demonstrate that the frequency seems to be underestimated. Deepening this topic may result useful in adequately managing this hernia type.